Penetapan Kadar Flavonoid Total berbagai Variasi Pelarut Pada Ekstrak Beras Hitam (Oryza Sativa L.Indica) Dengan Metode Spektrofotometri UV-Vis - Mahbub, Khafid; Novitasari , Novitasari (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2025)
Black rice (Oryza sativa L. Indica) is known to have a high anthocyanin compound content, and is included in the flavonoid compound group. The flavonoid content in an extract can be taken using an appropriate solvent. This shows that quality control is needed for the quality of the simplicia and the type of solvent, so that it can obtain quality secondary metabolites. The reason for this study was to determine the effect of 96% ethanol, methanol and acetone solvents on the flavonoid content of black rice extract. Black rice extract was analyzed qualitatively and the amount of flavonoid content. Quantitative testing of the amount of flavonoids used the UV-Vis spectrophotometry method. The results were analyzed using the One Way Anova strategy with a confidence level of 95%. The results showed that 96% ethanol, methanol and acetone extracts of black rice contained flavonoids, alkaloids, tannins, saponins and terpenoids. Theresults of the overall flavonoid test using the UV-Vis spectrophotometry strategyfrom 96% ethanol, methanol and acetone extracts of black rice were 8.6355 mg QE / g, respectively; 8.3713 mg QE/g and 22.4559 mg QE/g. The results of the Tukey One Way Annova test showed that the difference in solvent types had a significant effect on the flavonoid content of black rice extract with a significance value of 0.000 (p<0.05). Acetone solvents were effective in extracting flavonoid compounds compared to  methanol and 96% ethanol solvents